Bioconnections as Enablers of Regenerative Circularity for the Built Environment - Sala Benites, Henrique (2021)
Learning from nature may be the most important step towards improving cities in the context of environmental and climate issues. However, many of the current approaches to make cities greener or more sustainable are still linear and insufficient to deal with these growing challenges. In this scenario, the adoption of regenerative and circular lenses for the built environment may foster a more holistic development based on what is good rather than what is less bad. In this article, we propose that bioconnectivity or bioconnections—a nature-focused approach based on biophilic design, biomimetics, and ecosystem services—may be an important enabler for the regeneration of the ecological and social boundaries of the planetary boundaries and doughnut economics models. We examine the literature to identify in what ways bioconnections could facilitate circular and regenerative processes for the local scale of the built environment domain. We complement the discussion with some real-world examples from selected urban communities or interventions in existing urban areas around the globe that claim a green approach. In the end, we propose a framework of relevant bioconnections for the built environment that could facilitate addressing ecological and social boundaries at the local urban scale and facilitate processes of regenerative transitions towards thriving communities.